The accreditation process of careers in MERCOSUR: would the veterinary career in Uruguay achieve accreditation in accordance with the required standards of the Argentinian and Brazilian agencies? - José Passarini; Pablo Juri; Claudia Borlido; Enrique Nogueira (Universidad Nacional de Educación a Distancia (UNED), 2015)
MERCOSUR created the ARCU-SUR system as a regional mechanism for accreditation of undergraduate programmes. The Veterinary career in Uruguay achieved accreditation by ARCU-SUR in 2010. As re-accreditation approaches an evaluation of the career with the Brazilian and Argentinian national standards of accreditation was simulated due to their strong influence on the definition of the regional criteria. Institutional self-assessment was updated and compared with the accreditation indicators of the Brazilian and Argentinian agencies. The idea of quality of the accreditation system in Brazil emphasizes the training of the teaching staff while in Argentina emphasizes the teaching and learning processes. The career could achieve accreditation with the Argentinian parameters but should improve aspects of the academic training of their teachers to achieve accreditation in Brazil. This work made it possible to adjust the Development Plan of the Faculty of Veterinary Medicine.